High-temperature self-healing composite silicon carbon electrode and preparation method thereof
By blending graphite and silicon in the negative electrode material of lithium-ion batteries with different particle sizes and using supersonic spray liquid metal technology at high temperatures, the problem of volume expansion of silicon materials during charging and discharging is solved, and the cycle stability of the battery is improved and energy density, and achieve high temperature self-healing effect.
Patent Information
- Application Number
- CN202411694028.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The volume expansion of silicon materials in lithium-ion batteries during charging and discharging is severe, resulting in damage to the electrode structure, poor circulation performance and insufficient conductivity.
By blending graphite with silicon material with different particle sizes and supersonic spraying of liquid metal on the negative electrode active layer, the liquid metal melts at high temperature to repair the gap between the electrode surface and the negative electrode material, and inhibit the volume expansion of the silicon-based material. and evenly distribute lithium ions.
It significantly improves the cyclic stability, rate performance and energy density of the electrode, extends the service life of the battery, and achieves the effect of high-temperature self-healing.
Smart Images

Figure BDA0005151688730000091 
Figure BDA0005151688730000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium-ion batteries, and in particular to a high-temperature self-healing composite silicon-carbon electrode and a preparation method thereof. Background Art
[0002] With the continuous growth of global energy demand and reliance on renewable energy, the performance of lithium-ion batteries needs to be further improved, especially in electric vehicles and large-scale energy storage applications, which put forward higher requirements on the energy density, power density and cycle life of batteries. Among the various components of lithium-ion batteries, the performance of negative electrode materials has a crucial impact on the overall performance of the battery.
[0003] At present, the negative electrode materials of commercial lithium-ion batteries are mainly graphite-based carbon materials. Graphite negative electrode materials have good conductivity and low lithium insertion potential (close to 0.1V vs.Li / Li + ) and its structure is stable during the charge and discharge process, so it is widely used in lithium-ion batteries. However, the theoretical specific capacity of graphite is only 372mAh / g, which is difficult to meet the needs of future high-energy density batteries. Therefore, the development of negative electrode materials with higher specific capacity has become a research hotspot. Among many new negative electrode materials, silicon (Si) is considered to be one of the most promising next-generation lithium-ion battery negative electrode materials due to its extremely high theoretical specific capacity (about 4200mAh / g). Silicon can form silicon-lithium alloy (Li-Si) with lithium during the charge and discharge process. x Silicon (Si) has a theoretical specific capacity far exceeding that of traditional graphite materials. However, silicon materials also face many challenges in practical applications. The main problem is that their volume expands violently during the charge and discharge process (up to 300% or more), which leads to the destruction of the electrode structure, and then causes problems such as electrode pulverization and poor cycle performance. In addition, silicon materials have poor conductivity and are prone to form unstable solid electrolyte interface (SEI) films during the charge and discharge process, further affecting the cycle stability and coulombic efficiency of the battery.
[0004] In order to solve the problem of volume expansion and poor cycle stability of silicon materials during charging and discharging, researchers have proposed a variety of modification strategies, among which silicon-carbon composites (Si / C) are considered to be one of the most promising solutions. Silicon-carbon composites combine silicon with carbon materials and utilize the conductivity, structural stability and good lithium insertion properties of carbon materials to effectively alleviate the problem of volume change of silicon during charging and discharging, and improve the cycle stability and conductivity of the electrode. Despite this, there are still some challenges in practical applications, such as how to strike a balance between silicon content and electrode stability, and how to achieve a large-scale, low-cost preparation process.
[0005] Nano-silicon materials can effectively reduce the impact of volume expansion by reducing the size of silicon particles. In addition, encapsulating silicon materials in carbon materials or embedding silicon materials in porous carbon structures can further improve the structural stability and conductivity of the materials. Some studies have also attempted to dope carbon materials by introducing other elements (such as oxygen, nitrogen, phosphorus, etc.) to further optimize the electrochemical properties of silicon-carbon composites.
[0006] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0007] The purpose of the present invention is to provide a high-temperature self-healing composite silicon-carbon electrode, which effectively improves the compaction density by blending graphite with silicon materials of different particle sizes, and uniformly distributes lithium ions while controlling the volume deformation to bring about stress changes by using a liquid metal spray layer. The liquid metal can melt at high temperatures, repair the gap between the electrode surface and the negative electrode material, effectively inhibit the volume expansion of the silicon-based material and the shedding of the current collector, and improve the cycle and rate performance of the battery.
[0008] The above technical objectives of the present invention are achieved through the following technical solutions:
[0009] A high-temperature self-healing composite silicon-carbon electrode comprises a copper foil, a negative electrode active layer is coated on both sides of the copper foil, liquid metal is provided on the negative electrode active layer by supersonic spraying, the thickness of the liquid metal is micron-level, and the liquid metal is condensed and rolled in the gap of the negative electrode active layer; specifically, the thickness of the single-sided negative electrode slurry is 170-300um, and the compaction density of the uncompacted negative electrode after drying is 0.9-1.2g / cm 3 At this time, the negative electrode active material and binder particles are loosely arranged in disorder, so there are many nano-sized gaps. The present invention uses supersonic spraying of liquid metal on the negative electrode active layer, and the thickness of the liquid metal is micron-level. After hot spraying and rolling, micro-nano-level liquid metal particles fall on the surface, a part of which is pressed between the negative electrode active materials, and the rest covers the outermost surface layer of the electrode, which can effectively improve the overall structural density.
[0010] Gallium-based liquid metal is a low-freezing point metal material with a freezing point of 70-100°C. When heated, it changes from solid to liquid. After cooling again, the liquid metal changes from liquid to solid. The liquid metal layer sprayed on the surface of the silicon-carbon electrode sheet can be turned into a flowable and ductile state at high temperature. By applying pressure outside the battery, the flowing liquid metal can repair the broken silicon material.
[0011] The negative electrode active layer is prepared by coating the negative electrode slurry. The negative electrode slurry is prepared by mixing small-particle graphite, graphite, silicon material, binder and deionized water. The mass ratio of small-particle graphite, graphite and silicon material is 0.5-1:1.5-3:6-8. The viscosity of the negative electrode slurry is 3000-6000 mPa·s. The single-sided loading amount of the negative electrode slurry on the copper foil surface is 5-10 mg / cm 2 The three materials are mixed as the active material of the negative electrode slurry. The mixed materials with different particle sizes can fill each other's gaps during the compaction process, increase the electrode compaction density, and to a certain extent inhibit the volume expansion of silicon materials. The addition of small-particle graphite can to a certain extent improve the rate performance of the electrode. Compared with the slurry coating of each material separately, it takes less time and can achieve the purpose of high compaction and improved rate performance.
[0012] Among them, the specific capacity of silicon material is high, which can theoretically reach about 4200mAh / g. The present invention can significantly improve the overall specific capacity of the negative electrode by setting the silicon content in a relatively high range (6 to 8), thereby improving the energy density of the battery. Small-particle graphite and ordinary graphite are distributed together, which can optimize the interface between silicon and electrolyte in the electrode. Small-particle graphite has better filling ability and can effectively fill the gaps between ordinary graphite and silicon materials, thereby improving the overall compaction density of the slurry. Ordinary particle graphite can construct a good electronic conductive channel in a multi-scale structure. This optimized combination of particle sizes increases the compaction density of the active material in the electrode, which is beneficial to improving the energy density while retaining good conductivity and uniformity of the ion channel.
[0013] The viscosity within the range of 3000 to 6000 mPa·s can ensure that the suspension and distribution of active material particles (graphite, silicon) in the slurry will not cause excessive sedimentation, ensure that the distribution of different particles in the electrode is more uniform, and help to form a denser and more uniform active material layer after coating and calendering, thereby improving the overall mechanical strength and electrochemical performance of the electrode.
[0014] Preferably, the particle size of the small-particle graphite is 3 to 6.5 μm, the graphite includes at least one of natural graphite and artificial graphite, and the particle size is 7.5 to 27 μm; the silicon material is nano-silicon, micro-silicon, SiO x At least one of the following: the binder is at least one of polyacrylonitrile, polyacrylic acid, sodium alginate, and sodium carboxymethyl cellulose.
[0015] Preferably, the copper foil is any one of a smooth copper foil, a carbon-coated copper foil, and a graphite-coated copper foil.
[0016] Preferably, the liquid metal comprises a mixture of at least one metal selected from indium, tin, bismuth, and zinc and gallium metal, wherein the mass ratio of gallium is 20% to 50%, and the melting point of the liquid metal is 70 to 100°C. This temperature does not belong to the conventional operating temperature range of lithium-ion batteries, but the battery components can withstand this temperature range, so the liquid metal layer can be heated to undergo a solid-liquid phase transition, the broken electrode material after the cycle can be repaired, the battery electrochemical performance can be restored, and the high-temperature self-healing of the negative electrode sheet can be achieved, while avoiding spontaneous state transitions during normal operation of the battery. In order to keep the outermost liquid metal coating of the negative electrode in a solid state within the normal operating temperature range of the lithium-ion battery, unlike most room temperature liquid metals, the gallium metal content used in the present invention is relatively low, so that the overall melting point of the alloy is maintained at 70 to 100°C to ensure normal operation of the battery.
[0017] The second purpose of the present invention is to provide a method for preparing a high-temperature self-healing composite silicon-carbon electrode, so as to solve the problem that the silicon-based negative electrode in the current lithium-ion battery expands in volume during the charging and discharging process and the battery cycle stability is poor, reduce the expansion failure of the silicon-carbon negative electrode and increase the service life.
[0018] The above technical objectives of the present invention are achieved through the following technical solutions:
[0019] A method for preparing a high-temperature self-healing composite silicon-carbon electrode comprises the following steps:
[0020] S01: Small-particle graphite, graphite and silicon materials are mixed in proportion as negative electrode active materials, and a binder and deionized water are added to prepare a negative electrode slurry. The viscosity of the prepared negative electrode slurry is 3000-6000 mPa·s. The negative electrode slurry is coated on both sides of the copper foil surface, and the single-side load is 5-10 mg / cm 2 , forming a negative electrode active layer;
[0021] S02: The temperature of the blast oven at the rear end of the coating machine head is set at 90-110°C. The copper foil including the negative electrode active layer is dried and wound while coating. The copper foil is placed on the unwinder after drying, passed through the roller press and wound on the winder.
[0022] S03: Add liquid metal into the supersonic jet gas chamber, and evenly spray the atomized and broken micro-nano liquid metal droplets on the surface of the negative electrode active layer between the unwinder and the roller press through the nozzle; and then it is rolled together with the dried negative electrode slurry; the present invention performs supersonic spraying between the unwinder and the roller press, and at this time the liquid metal is close to its melting point or semi-molten state, has high fluidity, and can be more evenly filled into the microscopic gaps of the negative electrode material. In the process of entering the roller press, due to the short transmission path, the liquid metal is still in a relatively active state, which not only helps the liquid metal to better fit, but also can improve the density of the negative electrode material itself.
[0023] During the cold pressing operation of the roller press, the liquid metal has not yet completely solidified. Due to the high fluidity of the liquid metal, the instantaneous pressure of the cold pressing can cause it to quickly fill the gaps in the negative electrode active material. This method not only utilizes the flow characteristics of the liquid metal, but also solidifies it in the gaps through cold pressing to form a denser bond. After cold pressing, since the roller press itself has no additional heating, the liquid metal will quickly cool down during the cold pressing process and quickly solidify from a semi-molten state, which can effectively prevent the reflux of the liquid metal and maintain its embedded morphology and structural stability.
[0024] S04: The roller press cold presses the surface of the negative electrode active layer sprayed with liquid metal droplets. The liquid metal with a thickness of microns is condensed and rolled into the gaps of the negative electrode material in the negative electrode active layer. After rolling, the spraying is repeated and the other side is cold pressed to obtain a high-temperature self-healing composite silicon-carbon electrode.
[0025] Preferably, in step S02, the tension of the winder and the unwinder is 20-35N, and the winding speed is 20-60mm / s.
[0026] Preferably, in step S03, the temperature inside the supersonic jet gas chamber is 110-150° C., and the nozzle temperature is 110-130° C. This step allows the liquid metal to remain in a liquid state at a temperature above the melting point and be broken into micron / nano particles, which are evenly sprayed onto the surface of the composite silicon-carbon negative electrode sheet in the form of droplets.
[0027] Preferably, in step S04, the rolling pressure of the roller press is 5 to 10 tons, the winding speed of the winder and the unwinder is 20 to 60 mm / s, and the compaction density of the obtained composite silicon-carbon electrode is 1.3 to 1.9 g / cm 3 .
[0028] By means of the above technical solution, the present invention has at least the following beneficial effects:
[0029] (1) The present invention mixes graphites of different particle sizes with silicon materials as negative electrode active materials. The small-particle graphite can act as a conductive agent and can appropriately fill the gap between the large-particle graphite and the silicon material, thereby improving the material's ability to absorb and retain liquid, effectively improving the compaction of the electrode material, reducing the specific surface area of the electrode, and being beneficial to the first coulomb efficiency of the negative electrode sheet.
[0030] (2) The present invention utilizes supersonic jet gas in a high temperature environment to break up liquid metal, and uses a nozzle to spray micro-nano droplets, which can be evenly dispersed on the surface of the material.
[0031] (3) After the liquid metal is hot-sprayed, it is immediately cold-pressed using a roller press to roll the liquid metal onto the surface of the silicon-carbon negative electrode. After cooling, the rigid liquid metal can inhibit the expansion of the electrode. The excellent lithium affinity and high conductivity of the liquid metal can evenly distribute lithium ions during charging, alleviating the battery capacity attenuation and the formation of lithium dendrites at high rates. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is described in detail below through specific embodiments and comparative embodiments.
[0033] The term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0034] In the embodiments of the present invention, the specific sources of various materials are as follows:
[0035] Reagents / Materials Commercial Origin Copper Foil Shenzhen Kejing graphite Shenzhen Kejing Silicon Materials Shenzhen Kejing Polyacrylonitrile China Reagent Network Polyacrylic acid China Reagent Network Sodium alginate Shenzhen Kejing Sodium Carboxymethyl Cellulose Shenzhen Kejing Liquid Metal Dongguan Huatai Metal Material Technology Co., Ltd.
[0036] Example 1
[0037] The specific preparation of the high temperature self-healing composite silicon-carbon electrode of this embodiment is as follows:
[0038] (1) The binder sodium alginate and deionized water were used to prepare the glue solution, and after the glue solution was completely dissolved, conductive graphite KS-6, graphite SAG-20 and nano-Si (mass ratio 0.5:1.5:8) were added as negative electrode active materials to prepare the negative electrode slurry with a solid content of 46% and a viscosity of 4230 mPa·s. The negative electrode slurry was coated on both sides of the smooth copper foil, and the single-side loading was 5.3 mg / cm 2 ;
[0039] (2) Place the dried composite silicon-carbon negative electrode roll on an unwinder, pass it through a roller press and wind it up on a winder with a tension of 25N;
[0040] (3) Gallium-indium-tin (mass ratio 5:3:2) alloy is added into a 120°C supersonic jet gas chamber, and the atomized and broken micro-nanoscale liquid metal droplets are evenly sprayed onto the surface of the composite silicon-carbon negative electrode between the unwinder and the roller press through a 100°C nozzle;
[0041] (4) The roller press was set to a pressure of 10 tons and a winding and unwinding speed of 20 mm / s. The composite silicon-carbon negative electrode sprayed with liquid metal droplets was cold pressed. The liquid metal with a thickness of 11 μm was condensed and rolled in the gap of the negative electrode material on the surface. After winding, the spraying was repeated and the other side was cold pressed to obtain a high-temperature self-healing composite silicon-carbon electrode with a compactness of 1.53 g / cm 3 Composite electrode sheet.
[0042] Example 2
[0043] The specific preparation of the high temperature self-healing composite silicon-carbon electrode of this embodiment is as follows:
[0044] (1) The adhesive solution was prepared by using polyacrylonitrile as binder and deionized water. After the adhesive solution was completely dissolved, conductive graphite KS-6, graphite SAG-20 and micronized Si (mass ratio 1:2:7) were added as negative electrode active materials to prepare negative electrode slurry with a solid content of 48% and a viscosity of 6136 mPa·s. The negative electrode slurry was coated on both sides of the smooth copper foil and the single-side loading was 5.2 mg / cm 2 ;
[0045] (2) Place the dried composite silicon-carbon negative electrode roll on an unwinder, pass it through a roller press and wind it up on a winder with a tension of 25N;
[0046] (3) Gallium-indium-tin-zinc (mass ratio 3:3:3:1) alloy is added into a 120°C supersonic jet gas chamber, and the atomized and broken micro-nanoscale liquid metal droplets are evenly sprayed onto the surface of the composite silicon-carbon negative electrode between the unwinder and the roller press through a 120°C nozzle;
[0047] (4) The roller press is set to a pressure of 10 tons and a winding and unwinding speed of 40 mm / s. The composite silicon-carbon negative electrode sprayed with liquid metal droplets is cold pressed. The liquid metal with a thickness of 6 μm is condensed and rolled in the gap of the negative electrode material on the surface. After winding, the spraying is repeated and the other side is cold pressed to obtain a high-temperature self-healing composite silicon-carbon electrode with a compactness of 1.51 g / cm 3 Composite electrode sheet.
[0048] Example 3
[0049] The specific preparation of the high temperature self-healing composite silicon-carbon electrode of this embodiment is as follows:
[0050] (1) The adhesive solution was prepared by using polyacrylonitrile as binder and deionized water. After the adhesive solution was completely dissolved, conductive graphite KS-6, graphite S360 and nano-Si (mass ratio 1:3:6) were added as negative electrode active materials to prepare negative electrode slurry with a solid content of 46% and a viscosity of 4230 mPa·s. The negative electrode slurry was coated on both sides of the smooth copper foil and the single-side loading was 5.3 mg / cm 2 ;
[0051] (2) Place the dried composite silicon-carbon negative electrode roll on an unwinder, pass it through a roller press and wind it up on a winder with a tension of 30N;
[0052] (3) Gallium, indium, bismuth (mass ratio 3:4:3) alloy is added into a 120°C supersonic jet gas chamber, and the atomized and broken micro-nanoscale liquid metal droplets are evenly sprayed onto the surface of the composite silicon-carbon negative electrode between the unwinder and the roller press through a 120°C nozzle;
[0053] (4) The roller press is set to a pressure of 10 tons and a winding and unwinding speed of 20 mm / s. The composite silicon-carbon negative electrode sprayed with liquid metal droplets is cold pressed. The liquid metal with a thickness of 11 μm is condensed and rolled in the gap of the negative electrode material on the surface. After winding, the spraying is repeated and the other side is cold pressed to obtain a high-temperature self-healing composite silicon-carbon electrode with a compactness of 1.6 g / cm 3 Composite electrode sheet.
[0054] Comparative Example 1
[0055] In this comparative example, no small-particle graphite is added, and the negative electrode active material is ordinary large-particle graphite and silicon material. The remaining steps are consistent with those in Example 3. The specific experimental steps are as follows:
[0056] (1) The binder polyacrylonitrile and deionized water were used to prepare the glue solution. After the glue solution was completely dissolved, graphite S360 and nano-Si (mass ratio 4:6) were added as negative electrode active materials to prepare the negative electrode slurry with a solid content of 46% and a viscosity of 3855 mPa·s. The negative electrode slurry was coated on both sides of the smooth copper foil and the single-side loading was 5.3 mg / cm 2 ;
[0057] (2) Place the dried composite silicon-carbon negative electrode roll on an unwinder, pass it through a roller press and wind it up on a winder with a tension of 30N;
[0058] (3) Gallium, indium, bismuth (mass ratio 3:4:3) alloy is added into a 120°C supersonic jet gas chamber, and the atomized and broken micro-nanoscale liquid metal droplets are evenly sprayed onto the surface of the composite silicon-carbon negative electrode between the unwinder and the roller press through a 120°C nozzle;
[0059] (4) The roller press is set to a pressure of 10 tons and a winding and unwinding speed of 20 mm / s. The composite silicon-carbon negative electrode sprayed with liquid metal droplets is cold pressed. The liquid metal with a thickness of 11 μm is condensed and rolled in the gap of the negative electrode material on the surface. After winding, the spraying is repeated and the other side is cold pressed to obtain a high-temperature self-healing composite silicon-carbon electrode with a compactness of 1.6 g / cm 3 Composite electrode sheet.
[0060] Comparative Example 2
[0061] In this comparative example, no gallium-based alloy is sprayed on the negative electrode surface, and the remaining steps are consistent with those of Example 3. The specific experimental steps are as follows:
[0062] (1) The adhesive solution was prepared by using polyacrylonitrile as binder and deionized water. After the adhesive solution was completely dissolved, conductive graphite KS-6, graphite S360 and nano-Si (mass ratio 1:3:6) were added as negative electrode active materials to prepare negative electrode slurry with a solid content of 46% and a viscosity of 4230 mPa·s. The negative electrode slurry was coated on both sides of the smooth copper foil and the single-side loading was 5.3 mg / cm 2 ;
[0063] (2) Place the dried composite silicon-carbon negative electrode roll on an unwinder, pass it through a roller press and wind it up on a winder with a tension of 30N;
[0064] (3) The roller press was set to a pressure of 10 tons and a winding and unwinding speed of 20 mm / s to obtain a compaction of 1.6 g / cm 3 Composite electrode sheet.
[0065] Comparative Example 3
[0066] In this comparative example, no gallium-based alloy is sprayed on the negative electrode surface, and the silicon material is micron silicon. The remaining steps are consistent with those of Example 2. The specific experimental steps are as follows:
[0067] (1) The adhesive solution was prepared by using polyacrylonitrile as binder and deionized water. After the adhesive solution was completely dissolved, conductive graphite KS-6, graphite SAG-20 and micronized Si (mass ratio 1:2:7) were added as negative electrode active materials to prepare negative electrode slurry with a solid content of 48% and a viscosity of 6136 mPa·s. The negative electrode slurry was coated on both sides of the smooth copper foil and the single-side loading was 5.2 mg / cm 2 ;
[0068] (2) Place the dried composite silicon-carbon negative electrode roll on an unwinder, pass it through a roller press and wind it up on a winder with a tension of 25N;
[0069] (3) The roller press was set to a pressure of 10 tons and a reeling and unreeling speed of 40 mm / s to obtain a compaction of 1.51 g / cm 3 Composite electrode sheet.
[0070] Test Data
[0071] The negative electrode sheets prepared from the composite negative electrodes obtained in the examples and comparative examples were assembled into button-type batteries according to the button-type lithium-ion battery preparation process familiar to technicians in the industry for electrochemical performance testing. The test results are shown in Table 1.
[0072] The composite materials prepared in Examples 1 to 3 of the present invention and Comparative Examples 1-2 are respectively assembled into button batteries and marked accordingly: the button battery assembled from the composite material of Example 1 is marked as A1, the button battery assembled from the composite material of Example 2 is marked as A2, the button battery assembled from the composite material of Example 3 is marked as A3, the button battery assembled from the composite material of Comparative Example 1 is marked as B1, the button battery assembled from the composite material of Comparative Example 2 is marked as B2, and the button battery assembled from the composite material of Comparative Example 3 is marked as B3.
[0073] 1. First coulombic efficiency, rate performance and cycle retention at room temperature
[0074] The button batteries A1, A2, A3, B1, B2, and B3 were placed on the Wuhan Blue Electric CT2001A battery tester for testing. The first charge and discharge were at a rate of 0.05C and a rate of 0.1C. The first coulomb efficiency was the ratio of the charge capacity to the discharge capacity. Constant current charge and discharge tests were performed at different rates, with a voltage range of 0.005V to 2V. The first coulomb efficiency and the capacity, capacity retention rate, and cycle stability at different rates were measured as shown in Table 1:
[0075] Table 1 Electrochemical performance of composite negative electrode sheets of Examples 1-3 and Comparative Examples 1-2
[0076]
[0077] It can be seen from Table 1 that the lowest first coulombic efficiency of the composite silicon-carbon negative electrode prepared in Examples 1-3 is 88.5%, and the lowest discharge capacity retention rate at 1C rate is 80.6%. This is mainly because compared with micron silicon and nano silicon, there is still a certain volume change during the charge and discharge process; while the highest first discharge efficiency of the composite negative electrode material prepared in the comparative example is only 82.7%.
[0078] The first charge and discharge efficiency and 1C rate discharge capacity retention rate of the button-type battery of the high-temperature self-healing composite silicon-carbon electrode of the present invention are significantly higher than those of comparative examples 2-3; and the cycle performance of the composite negative electrode material prepared by the present invention is higher than that of comparative examples 1-3.
[0079] That is, the composite electrode of the present invention is mixed with graphite of different particle sizes and silicon material as negative electrode active materials. The small-particle graphite can act as a conductive agent and can appropriately fill the gap between the large-particle graphite and the silicon material, effectively improving the compaction of the electrode material, which is beneficial to improving the first coulomb efficiency and can also improve the rate performance. The gallium-based alloy is heated and sprayed and cold-pressed on the surface of the base silicon-carbon negative electrode, which can inhibit the expansion of the electrode during charge and discharge cycles. The excellent lithium affinity and high conductivity of the liquid metal can evenly distribute lithium ions during charging, alleviating the battery capacity attenuation and the generation of lithium dendrites at high rates.
[0080] 2. Electrode self-healing ability (capacity recovery) after the battery is cycled 200 times at 80°C
[0081] The lithium ion batteries prepared in Example 1-3 and Comparative Example 1-3 after 200 cycles at 0.5C were placed in a forced air drying oven at 85°C for 12 hours. After cooling to room temperature, they were charged and discharged again at 0.5C for 10 cycles. The capacity of the last cycle was compared with the discharge capacity at the initial 0.1C rate.
[0082] Table 2 Capacity recovery of the batteries of Examples 1-3 and Comparative Examples 1-3 at 80°C
[0083]
[0084] It can be seen from Table 2 that the negative electrode sheets prepared in Examples 1-3 and Comparative Example 1 can recover a certain capacity after standing at high temperature, while the negative electrode whose surface is not sprayed with liquid metal is difficult to recover the capacity by standing at high temperature. This indicates that the gallium-based metal can repair the base negative electrode after cycling at high temperature and realize self-healing of the electrode sheet.
[0085] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A high-temperature self-healing composite silicon-carbon electrode, characterized in that: It comprises a copper foil, wherein both sides of the copper foil are coated with a negative electrode active layer, and liquid metal is applied to the negative electrode active layer by supersonic spraying, and the liquid metal is condensed and rolled in the gap of the negative electrode active layer; The negative electrode active layer is prepared by coating the negative electrode slurry, wherein the negative electrode slurry comprises small-particle graphite, graphite, silicon material, a binder and deionized water, the mass ratio of the small-particle graphite, the graphite and the silicon material is 0.5~1:1.5~3:6~8, and the viscosity of the negative electrode slurry is 3000~6000mPa·s.
2. A high temperature self-healing composite silicon-carbon electrode according to claim 1, characterized in that: The negative electrode slurry has a single-sided loading of 5-10 mg / cm 2 .
3. The high temperature self-healing composite silicon-carbon electrode according to claim 1, characterized in that: The particle size of the small-particle graphite is 3-6.5 μm, the graphite includes at least one of natural graphite and artificial graphite, and the particle size is 7.5-27 μm; the silicon material is nano-silicon, micro-silicon, SiO x At least one of .
4. The high temperature self-healing composite silicon-carbon electrode according to claim 1, characterized in that: The binder is at least one of polyacrylonitrile, polyacrylic acid, sodium alginate and sodium carboxymethyl cellulose.
5. The high temperature self-healing composite silicon-carbon electrode according to claim 1, characterized in that: The copper foil is any one of a smooth copper foil, a carbon-coated copper foil and a graphite-coated copper foil.
6. The high temperature self-healing composite silicon-carbon electrode according to claim 1, characterized in that: The liquid metal comprises a mixture of at least one metal selected from the group consisting of indium, tin, bismuth and zinc and gallium metal, wherein the mass ratio of gallium is 20% to 50%, and the melting point of the liquid metal is 70 to 100°C.
7. The method for preparing a high-temperature self-healing composite silicon-carbon electrode according to any one of claims 1 to 6, characterized in that: The following steps are involved: S01: small-particle graphite, graphite and silicon material are mixed in proportion, a binder and deionized water are added to prepare a negative electrode slurry, and the negative electrode slurry is coated on both sides of the copper foil surface to form a negative electrode active layer; S02: placing the dried copper foil including the negative electrode active layer on an unwinder, passing through a roller press and winding up on a winder; S03: adding liquid metal into the supersonic jet gas chamber, and spraying the atomized and broken micro-nano-scale liquid metal droplets uniformly on the surface of the negative electrode active layer between the unwinder and the roller press through the nozzle; S04: The roller press cold presses the surface of the negative electrode active layer sprayed with liquid metal droplets. The liquid metal with a thickness of microns is condensed and rolled into the gaps of the negative electrode material in the negative electrode active layer. After rolling, the spraying is repeated and the other side is cold pressed to obtain a high-temperature self-healing composite silicon-carbon electrode.
8. The method for preparing a high-temperature self-healing composite silicon-carbon electrode according to claim 7, characterized in that: In step S02, the tension of the winder and the unwinder is 20-35N, and the winding speed is 20-60mm / s.
9. The method for preparing a high-temperature self-healing composite silicon-carbon electrode according to claim 7, characterized in that: In step S03, the temperature inside the supersonic jet gas chamber is 110-150°C, and the temperature of the nozzle is 110-130°C.
10. The method for preparing a high-temperature self-healing composite silicon-carbon electrode according to claim 7, characterized in that: In step S04, the rolling pressure of the roller press is 5-10 tons, the winding speed of the winder and the unwinder is 20-60 mm / , and the compaction density of the obtained composite silicon-carbon electrode is 1.3-1.9 g / cm³.
Citation Information
Patent Citations
Negative pole piece of lithium ion battery, and lithium ion battery using the negative pole piece
CN109585781A
Liquid metal-based self-healing lithium battery negative electrode, preparation method and lithium ion battery
CN110061190A
Self-repairing lithium ion battery negative electrode material and preparation method thereof
CN112054176A
Silicon negative electrode material of lithium ion battery and preparation method and application thereof
CN112614976A
Liquid metal silicon-based composite negative electrode material and preparation method thereof
CN118299537A
Cited By
Preparation method of pre-lithiation negative electrode for solid-state battery and solid-state battery
CN120376579A